Characterization of Seismic Levee Fragility Using Field Performance Data. Issue 1 (February 2016) - Kwak, Dong Youp; Stewart, Jonathan P.; Brandenberg, Scott J.; Mikami, Atsushi
We characterize the seismic fragility of levees along the Shinano River system in Japan using field performance data from twoM 6.6 shallow crustal earthquakes. Levee damage is quantified based on crack depth, crack width, and crest subsidence for 3, 318 levee segments each 50 m long. Variables considered for possible correlation to damage include peak ground velocity ( PGV ), geomorphology, groundwater elevation, and levee geometry. Seismic levee fragility is expressed as the probability of exceeding a damage level conditioned on PGV alone and PGV in combination with other predictive variables. The probability of damage (at any level) monotonically increases from effectively zero for PGV < 14 cm/s to approximately 0.5 for PGV ≈ 80 cm/s. Of the additional parameters considered, groundwater elevation relative to the levee base most significantly affects fragility functions, increasing and decreasing failure probabilities (relative to the PGV -only function) for shallow and deep groundwater conditions, respectively.